Recognition of myocardial rupture in emergency: case report: Reconocimiento de rotura miocárdica en emergencia: reporte de caso - Calcino Cuela, Jessica (2019)
A 86-year old female patient with hypertension was admitted to emergency due to chest pain, dyspnea, hypotension and bradycardia with confusional symptoms. The electrocardiogram and the laboratory are compatible with acute non-Q myocardial infarction, with a left ventricular ejection fraction of 20% in the ultrasound, with pericardial effusion and hyperechoic mass compatible with a clot. The diagnosis was a low cardiac output due to an evolutive non-Q myocardial infarction with myocardial rupture. The patient required endotracheal intubation and mechanical ventilation, evolved with cardiac arrest and was resuscitated without success. The diagnosis and timely management of cardiac rupture is discussed as a mechanical complication of acute myocardial infarction. DOI:10.25176/RFMH.v19.n2.2076